Gray Matter Changes in Late Life Depression—a Structural MRI Analysis - Andreescu, Carmen; Butters, Meryl A; Begley, Amy; Rajji, Tarek; Wu, Minjie; Meltzer, Carolyn C; Reynolds, Charles F; Aizenstein, Howard (Neuropsychopharmacology (New York, N.Y.), 2008)
Multiple brain morphometric changes have been reported in late-life depression (LLD), mostly in studies comparing volumes of circumscribed brain areas. The aim of our study is to characterize the volumetric changes of multiple gray matter regions in relation to age of onset/duration of illness. We predicted that the association of gray matter volumes with total duration of illness and age of onset would differ depending on whether the region was susceptible to the toxic effects of chronic exposure to cortisol or to the vascular/neurodegenerative changes accompanying prodromal dementia. Seventy-one elderly depressed subjects were studied along with thirty-two comparison subjects. High-resolution T1-weighted brain MRIs were processed using an automated labeling pathway technique. To protect against type-I error, we combined the right and left hemisphere volume data. We sampled 24 regions of interest (ROIs). We used the primary visual cortex volume to normalize for individual variations in brain size. LLD Subjects had smaller volumes than non-depressed subjects in 17 of the 24 examined ROIs. Shorter duration of illness and later age of onset was correlated with smaller volumes of parahippocampal area and parietal inferior area. A later age of onset was also correlated with smaller volumes of several frontal and temporal areas, cingulum, and putamen. Our findings support a dementia prodrome model more strongly than a toxic stress model in this group of subjects. However, it remains likely that both processes as well as other factors contribute to the heterogeneity of volumetric brain changes in LLD.